PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VISUAL BASIC 6.0 PADA POKOK BAHASAN LAJU REAKSI UNTUK KELAS XI SMA/SEDERAJAT - Syarifah Dairatul Hasanah M; Erviyenni '; Rasmiwetti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Development of learning media based on Visual Basic 6.0 on the topic rate of reaction has been done. Development of learning media to get a valid learning media. The research and development method used ADDIE models which consists of five stages are analysis, design, development, implement and evaluate. Data collected technique used validation sheet was given to three validators (two of media expert and a matter experts). The results showed score of the designing aspectswas 3,73; pedagogic aspects was 4; the content aspects was 3,83; the ease of use aspects was 3,93.Average score overall validation of learning media based on Visual Basic 6.0 on the topic rate of reactionwas3,87.Average score overall validation of learning media based on Visual Basic 6.0 show that this media is valid and can be use in learning process.Key Words: Learning Media, Visual Basic 6.0, Rate of Reaction